Stepwise B-cell-dependent expansion of T helper clonotypes diversifies the T-cell response - Julia Merkenschlager (Nature Portfolio, 2016)
During an immune response, CD4+ T cell repertoire is thought to increase in avidity at the expense of diversity. Here the authors show that B cells act as antigen-presenting cells to boost the development of low-avidity T cell clones, diversifying the T cell repertoire at late stages of the response.